Outcomes of in vitro fertilization–embryo transfer in women with diminished ovarian reserve after growth hormone pretreatment. (1st November 2020) - Chen, Yanrong; Tao, Liyuan; Lin, Yihua; Li, Xiaoxue; Ma, Caihong
Abstract: The study was to evaluate the in vitro fertilization–embryo transfer (IVF-ET) outcomes in women with diminished ovarian reserve (DOR) after pretreatment with growth hormone (GH). Retrospective propensity score matching study, which included 92 women received GH over 4 weeks pretreatment before their subsequent IVF cycles and 92 matched controls who underwent IVF cycles between July 2017 and August 2018. The evaluation parameters included ovarian response, embryological parameters, and pregnancy outcomes after embryo transfer (ET). The mean number of retrieved oocytes and transferable day-3 embryos were significantly higher after GH pretreatment. The implantation rate, clinical pregnancy rate, and ongoing pregnancy rate per fresh ET cycle were similar between the GH group and control group. In women who either achieved pregnancy or utilized all the embryos resulting from the index stimulation cycle, the cumulative clinical pregnancy rate was significantly higher in women with GH compared to the control group. 4 weeks pretreatment with GH could increase ovarian response to stimulation and then improved IVF-ET outcomes in women with DOR.